Transplanting Time of Strawberry Runners Influences Plant Growth, Post-harvest Quality and Antioxidant Properties of Different Cultivars Grown in Subtropical Highlands of Azad Jammu and Kashmir (Plant Bulletin, 2022)
Strawberry is a well-known aggregate fruit. It has an exceptional mouth feel taste with high nutritional characteristics. Transplanting time of strawberry runners mainly affects growth of plant, yield and quality of fruit. But transplantation time for different cultivars of strawberries is not yet standardized in Azad Kashmir. Thus, the study was designed to evaluate the field performance of three strawberry cultivars viz. Chandler, Seascape and Tribute on three different transplanting dates i.e., 15th March, 30th March and 15th April. Plant vegetative growth, fruit yield and antioxidant characteristics were determined. Transplantation time significantly influenced most of the parameters under study. Runners transplanted on 30th March showed the highest survival percentage (90.0%), number of leaves per plant (9.97) in cv. Chandler followed by cv. Seascape and cv. Tribute. Runner production per plant was high in the runners transplanted on 15th March in all the cultivars under observation. Total soluble solids, sugars, vitamin C, anthocyanin and antioxidant activity was significantly enhanced in the fruit of plants transplanted on 30th March. Overall, results suggested that transplantation of strawberry runners from 15th March to 30th March is ideal for gaining high yield and nutritious strawberry fruit in the area of Azad Kashmir.
Keywords: Anthocyanin content; arthropods; agriculture; flavonoids; Chandler; Seascape; strawberry